2000
DOI: 10.1021/jo9914061
|View full text |Cite
|
Sign up to set email alerts
|

Solvolysis of 2-Bicyclo[3.2.2]nonyl p-Toluenesulfonate. Evidence for the Formation of Classical Carbocation Intermediates

Abstract: The solvolysis rate of 2-bicyclo[3.2.2]nonyl p-toluenesulfonate (6-OTs) was nearly equal to that of cycloheptyl p-toluenesulfonate in 2,2,2-trifluoroethanol (TFE). This indicates that the ethylene bridge in 6-OTs does not significantly enhance the rate and that 6-OTs ionizes without anchimeric assistance. The solvolysis of [1-(13)C]-2-bicyclo[3.2.2]nonyl p-toluenesulfonate in methanol or TFE gave 2-substituted bicyclo[3.2.2]nonane, exo-2-substituted bicyclo[3.3.1]nonane, 2-bicyclo[3.2.2]nonene (10), and 2-bicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Okazaki et al reported the partial 13 C NMR chemical shifts and attached protons for their starting materials and products without giving assignments. Reference is made to the use of “authentic” samples without further details.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okazaki et al reported the partial 13 C NMR chemical shifts and attached protons for their starting materials and products without giving assignments. Reference is made to the use of “authentic” samples without further details.…”
Section: Resultsmentioning
confidence: 99%
“…In a recently published study, Okazaki et al utilized carbon-13 labeling to study the solvolysis and rearrangement of 2-bicyclo[3.2.2]nonanyl tosylate in methanol and also 2,2,2-trifluoroethanol at 50 °C. They reported the formation of the ethers derived from the 2-bicyclo[3.2.2]nonanyl and 2-bicyclo[3.3.1]nonanyl systems.…”
Section: Introductionmentioning
confidence: 99%
“…To address the lower accuracy observed with some molecules containing aromatic carbons (3.4%), we added a paramagnetic relaxation agent. , For these studies, we employed a mixture of 3,5- and 2,5-dimethylphenol (Table ). Relaxation agents reduce longitudinal relaxation times, therefore improving quantitative 13 C NMR spectroscopic analysis. Oxygen (O 2 ) was chosen to avoid sample contamination. Accuracy compared to 1 H NMR spectroscopic integration improved from 2.5% to 0.7% when the sample was prepared from solvent that was saturated with O 2 prior to sample preparation.…”
mentioning
confidence: 99%
“…During the solvolysis study of 2-bicyclo[3.2.2]nonyl p -toluenesulfonates, Okazaki's group and Schafaer's team found that the solvolysis products of such bicycles are usually enriched with bicyclo[3.3.1]nonanes. 221–224 It was found that when 477 was solvolyzed in methanol and 2,2,2-trifluoroethanol (TFE) buffered with 2,6-lutidine, 2-bicyclo[3.3.1]nonene ( 479 ) (yield 15–47%) and exo -2-R-bicyclo[3.3.1]nonane (R = methoxy, 480 ; R = trifluoroethoxy, 481 ) were formed along with other bicycles in 12–23% yield. The solvolytic data indicated that these products were formed from the 2-bicyclo[3.2.2]nonyl cation ( 478 ), thereby unveiling the evidences for the formation of a classical carbocation intermediate (Scheme 110).…”
Section: Synthetic Approachesmentioning
confidence: 99%